The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1290/1071-2690(2002)038<0079:cpafdo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative PCR Analysis for Detection of Mycoplasma Infections in Continuous Cell Lines

Abstract: Mycoplasma contamination of cell lines is one of the major problems in cell culturing. About 15-35% of all cell lines are infected with a limited number of mycoplasma species of predominantly human, swine, or bovine origin. We examined the mycoplasma contamination status in 495 cell cultures by polymerase chain reaction (PCR) assay, microbiological culture method, and deoxyribonucleic acid-ribonucleic acid (DNA-RNA) hybridization, and in 103 cell cultures by PCR and DNA-RNA hybridization, in order to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 12 publications
1
106
1
1
Order By: Relevance
“…The use of two methods has been the most recommended strategy to minimize false results. PCR in combination with culture is the most widely recommended procedure (30). In the present study, PCR detected more infected samples than culture.…”
Section: Discussionmentioning
confidence: 49%
“…The use of two methods has been the most recommended strategy to minimize false results. PCR in combination with culture is the most widely recommended procedure (30). In the present study, PCR detected more infected samples than culture.…”
Section: Discussionmentioning
confidence: 49%
“…The presence of false positive results is considered as an important disadvantage of PCRbased methods especially in nested PCR (Cheong et al 2011). Although the hybridization technique is basically established on PCR method principles, (Uphoff and Drexler 2002). In a previous study by Mc Garrity et al mycoplasma contamination was evaluated in 30 cell lines using microbial and PCR methods, which respectively detected 10 and 14 positive ones.…”
Section: Discussionmentioning
confidence: 99%
“…The LOD of nested PCR was similar to the sensitivity of microbial culture and higher than for Mycoalert Ò . Uphoff and Drexler also reported that in comparison with microbial culture and DNA-RNA hybridization, molecular PCR technique could be considered as a sensitive, economic, accurate, precise, cheap, simple and rapid method for detection of mycoplasma contamination in cell cultures (Uphoff and Drexler 2002). On the other hand, according to the Young et al suggestion, at least two or three tests must be synchronously performed for contamination recognition (Young et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Mycoplasma contamination has been detected in 15-35% of cell lines deposited in some cell culture collections. 2 Although the manufacture of recombinant proteins and vaccines from cell lines has a good safety record, there have been reports of the contamination of production processes and viral vaccines by viruses most probably derived from contaminated media components and fetal calf sera. 3 -7 Porcine parvovirus has been isolated from commercial trypsin used in passaging of adherent cell lines.…”
Section: Relevant Issuesmentioning
confidence: 99%